Black heroes and heroines in cinema.Representations of Afro-American identities in the “Blaxploitation” movies - Drozdowicz, Jarema (Wydawnictwo Naukowe UAM, 2014)
The cinematic genre of Blaxploitation is a significant example of how the popular culture influences certain identity patterns. In this case the this relation is being examined on the issue of contemporary Afro-American identities. This paper attempts to answer the question of the mechanism of identity construction in the context of new media, and cinema in particular. Thus the Blaxploitation movies are being regarded here as a phenomenon which is in large extent typical for other identity constructions in the context of a global cultural change occurring in the last decades in the West.
Keywords: Blaxploitation; cinema; Afro-American identities; popular culture; blackness